The needs of vitamin in medical ill patients - Luciana B Sutanto (Indonesian Nutrition Association, 2022)
Vitamin deficiency is often appeared in medical ill patients. The vitamin deficiency can be deficiency favouring disease development, inadequacy or deficit worsening the condition, or deficiency as a result of disease. Recommendation number 1 from ESPEN micronutrient guideline 2022 is adequate amounts of all essential trace elements and vitamins shall be supplied to all patients receiving medical nutrition from the beginning of the period of nutritional support.